Modeling water flow through loamy soil containing an artificial macropore: effects of macropores dimensions and initial water content - Muhamad Askari, Muhamad Askari (2015)
Many studies have examined the individual macropores and their size effects on water flow and solute transport. However, the effects of macropore size on reducing surface runoff has not been scientically studied. The present study describes a laboratorium experiment and examine the effects of macropore dimensions and changes in initial soil water content on the cumulative infiltration and the occurrence of first time drainage. The water flow through a loamy soil (2mm sieved and 15% of initial water content) containing an artificial cylindrical macropore having 8 cm in diameter and 9 cm in height was observed through a soil column having 20 cm in diameter and 20 cm in height. HYDRUS 2D/3D was employed to simulate the water flow through the soil at 5 cm. 8 cm. and 10 cm in diameters: and 10 cm. 20 cm and 50 cm in heights of the macropore. Three contrasting initial soil water contents: 15%. 20%. and 25% was applied into the treatment of different sizes of macropore diameters. Overall, the observed cumulative infiltration agreed well with simulated one meanwhile the observed cumulative drainage fairly agreed with the simulated one. The simulation shows the wetter the initial water content the faster the drainage occurs on each size of macropore diameter. The doubling of macropore diameter size gives a response 10 the occurrence of first drainage as much as 150-160% faster on the same initial water content Increasing five times of macropore depth gives a response to the occurance of first drainage as much as 407% faster on the same initial water content and macropore diameter size.